ESSENCE OF THE ECONOMIC PERSONS’ CULTURE AND ITS ROLE IN THE ECONOMIC SOCIALIZATION - Zubiashvily, Irina (PSYCHOLOGICAL JOURNAL, 2019)
In the article the results of a theoretical research of the essence of the economic culture of the person as the most important condition for its economic socialization are analyzed. The research made it possible to define culture as an integral set of specifically integrated means of creative activity, creating cultural values and being a universal form of human social development, determining its internal and external sociocultural and socio-conscious relations with the outside world. It has been revealed that economic culture is one of the special spheres of culture, representing, in a way, a projection of the economy onto the cultural sphere, although it can be argued that culture is a projection onto the economic sphere. The essential properties of economic culture are manifested in the fact that, first, they cover tendencies, norms that have arisen from the needs of the economy; secondly, the main channel of influence on the economy is not any behavior, but, above all, economic behavior; thirdly, the economic culture is more focused on the management of people's behavior with a view to increasing a material well-being. It is noted that in the conditions of transformation of the economic system of Ukraine, the role and importance of the economic culture of society in the economic socialization of the population increases, the result of which can be a new economic culture of the person. It is emphasized that by associating economic socialization with the process of the formation of the person’s economic culture, it should be noted that culture is capable of transferring the values and attitudes of people from the spiritual to the material sphere, embodying values into reality. At the same time, it is important that the values governing the behavior and activities of the person in significant economic situations will affect the relations of economic subjects and, in general, the economic situation in the country. Nowadays, not creative work, but property and wealth, regardless of how they were obtained, are becoming increasingly important. It is proposed to draw attention to ensuring the moral content of many market values, the formation of a system of values of economic relations that rely on the human ones to avoid criminalization of the economy and economic relations, since the system of values included in the economic culture determines the process of economic socialization.